Surface-modified fibers, reinforcing fibers, and molded article using the same

JP2025026645AActive Publication Date: 2025-02-21KURARAY CO LTD

Patent Information

Application Number
JP2024215288
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-11-27
Filing Date
2024-12-10
Publication Date
2025-02-21
Estimated Expiration
2040-11-10

AI Technical Summary

Benefits of technology

【0010】 本発明は、レゾルシノール及びホルムアルデヒドを用いることなく、ゴムとの接着性を向上させることができる表面改質繊維、補強繊維及びそれを用いた成形体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026645000001
    Figure 2025026645000001
  • Figure 2025026645000002
    Figure 2025026645000002
  • Figure 2025026645000003
    Figure 2025026645000003
Patent Text Reader

Abstract

To solve the issue of insufficient adhesion strength when bonding fibers to rubber.SOLUTION: The present invention provides surface-modified fibers and reinforcing fibers that are capable of enhancing adhesion to rubber, without the use of resorcinol and formaldehyde, and a molded article using these fibers. The surface-modified fibers include fibers, and a surface-modifying layer covering at least a part of the surface of the fibers, with the solid surface zeta potential on the surface of the surface-modifying layer ranging from -20.0 to 30.0 mV.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a surface-modified fiber having excellent adhesion to rubber, a reinforcing fiber, and a molded article using the same. [Background technology]

[0002] Synthetic organic fibers such as polyethylene terephthalate (PET), nylon 66, vinylon, and rayon are inexpensive, strong, heat-resistant, durable, and lightweight, and therefore are used as reinforcing fibers for automobile tires and oil brake hoses. In order to fully utilize the excellent physical properties of rubber in these products (e.g., high strength and high elastic modulus), it is necessary to firmly bond the fibers and rubber.

[0003] As a method for firmly bonding fibers and rubber, a method using an adhesive called RFL, whose main components are resorcinol-formaldehyde resin and rubber latex, has been widely known (Patent Documents 1 and 2). However, since the formaldehyde contained in RFL is suspected of being carcinogenic and resorcinol is suspected of being an environmental hormone, there is a need to develop alternative materials that do not use these raw materials.

[0004] As an alternative material to RFL, for example, Patent Document 3 proposes a technology that uses an adhesive containing an adhesive compound having an unsaturated carbon bond and an epoxy group that reacts with a vulcanizing agent used in vulcanization of rubber. Patent Document 4 also proposes a technology that provides an active functional group layer by adding a blocked isocyanate compound and an epoxy compound to the first stage, and uses an adhesive component mainly composed of latex in the second stage. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 54-4976 [Patent Document 2] Japanese Patent Application Publication No. 58-2370 [Patent Document 3] JP 2011-111563 A [Patent Document 4] European Patent No. 3258006 Summary of the Invention [Problem to be solved by the invention]

[0006] The method using the adhesive described in Patent Document 3 has a problem that the adhesiveness is significantly inferior to the conventional method using RFL, and is poor in practical use. In addition, the treatment described in Patent Document 4 requires a step of providing an intermediate layer called a rubberized layer, and requires two-stage heat treatment at high temperature, so the treatment requires a lot of energy and there is a concern that the thermal degradation of the fiber may cause a decrease in reinforcing performance. Note that Patent Document 4 only describes a technology using an adhesive component mainly composed of latex, and does not describe the use of an adhesive component mainly composed of a conjugated diene rubber.

[0007] The present invention has been made in consideration of the above-mentioned conventional problems, and an object of the present invention is to provide a surface-modified fiber, a reinforcing fiber, and a molded article using the same that can improve adhesion to rubber without using resorcinol or formaldehyde. [Means for solving the problem]

[0008] As a result of intensive research to solve the above problems, the inventors have discovered that by attaching a specific compound to a fiber and adjusting the zeta potential of the fiber surface within a specific range, the affinity between the fiber and an adhesive component is increased, and as a result, the adhesion between the fiber and rubber is improved without using resorcinol or formaldehyde, and have completed the present invention.

[0009] That is, the present invention relates to the following [1] to

[14] . [1] A surface-modified fiber comprising a fiber and a surface-modified layer covering at least a portion of the surface of the fiber, the surface of the surface-modified layer having a solid surface zeta potential of -20.0 to 30.0 mV. [2] The surface-modified fiber according to [1], wherein the fiber is one or more types of fiber selected from polyester-based fibers, polyamide-based fibers, polyvinyl alcohol-based fibers, and regenerated cellulose-based fibers. [3] The surface-modified fiber according to [1] or [2], wherein the surface-modified layer contains a compound having a nitrogen-containing functional group. [4] The surface-modified fiber according to any one of [1] to [3], wherein the surface-modified layer contains a compound having a functional group derived from one or more selected from an oxazoline group, an oxazolidinone group, a carbodiimide group, a carbamide group, an amino group, and an aziridine group. [5] The surface-modified fiber according to any one of [1] to [4], wherein the amount of the surface-modified layer is 0.01 to 5.0 parts by mass per 100 parts by mass of the fiber used as the raw material. [6] A reinforcing fiber comprising the surface-modified fiber according to any one of [1] to [5] above and an adhesive layer containing a conjugated diene rubber covering at least a portion of the surface of the surface-modified fiber. [7] The reinforcing fiber according to [6], wherein the conjugated diene rubber has a number average molecular weight (Mn) of more than 2,000 and not more than 120,000. [8] The reinforcing fiber according to [6] or [7], wherein the conjugated diene rubber has, in its molecule, a monomer unit derived from one or more selected from butadiene, isoprene, and farnesene. [9] The reinforcing fiber according to any one of [6] to [8], wherein the conjugated diene rubber is a modified conjugated diene rubber having a hydrogen-bonding functional group in a portion of the conjugated diene rubber, and the hydrogen-bonding functional group is one or more selected from a hydroxy group, an epoxy group, an aldehyde group, an acetalized product of an aldehyde group, a carboxy group, a salt of a carboxy group, an esterified product of a carboxy group, an acid anhydride of a carboxy group, a silanol group, an esterified product of a silanol group, an amino group, an imidazole group, and a mercapto group.

[10] The reinforcing fiber according to any one of [6] to [9], wherein the adhesive layer further contains oil, and the oil has a vapor pressure of 10 Pa or less at 20° C.

[11] A molded article using the reinforcing fiber according to any one of [6] to

[10] above.

[12] The molded article according to

[11] , further comprising a rubber layer.

[13] The molded article according to

[11] or

[12] above, which is a tire, a belt or a hose.

[14] A molded article having a fiber, a surface modification layer, an adhesive layer, and a rubber layer in this order, wherein the adhesive strength between the adhesive layer and the rubber layer is 70 N or more per 25.4 mm width. Effect of the Invention

[0010] The present invention can provide a surface-modified fiber, a reinforcing fiber, and a molded article using the same, which can improve adhesion to rubber without using resorcinol or formaldehyde. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Surface modified fiber] The surface-modified fiber of the present invention comprises a fiber and a surface-modified layer covering at least a portion of the surface of the fiber, and is characterized in that the solid surface zeta potential of the surface of the surface-modified layer is -20.0 to 30.0 mV. According to the present invention, since the zeta potential of the solid surface is adjusted to the above range, a strong affinity is developed between the modified conjugated diene rubber contained in the adhesive component and the fiber, and the fiber, adhesive component, and rubber are firmly bonded to each other, resulting in improved adhesion between the fiber and rubber. In the present invention, a "surface modification layer covering at least a portion of the surface of the fiber" may mean an embodiment in which a surface modification layer is present on at least a portion of the surface of the fiber, for example, as a membrane or layer, or an embodiment in which the raw material of the fiber contains a component corresponding to the surface modification layer, and the component of the surface modification layer is present on a portion of the surface of the fiber itself.

[0012] From the viewpoint of improving the affinity between the fiber and the adhesive component, and thus improving the adhesion between the fiber and the rubber, the solid surface zeta potential on the surface of the surface modification layer is preferably -20.0 to 20.0 mV, more preferably -15.0 to 15.0 mV, even more preferably -10.0 to 12.0 mV, even more preferably -5.0 to 10.0 mV, even more preferably -5.0 to 9.0 mV, even more preferably -5.0 to 6.0 mV, and even more preferably -5.0 to 0 mV.

[0013] <Surface modification layer> The surface modification layer in the present invention is not particularly limited as long as it is composed of a compound that can adjust the solid surface zeta potential within the above range. For example, it is preferable that the surface modification layer is a layer containing a compound having a nitrogen-containing functional group, and specifically, it is preferable that the surface modification layer is a layer containing a compound having one or more functional groups selected from an oxazoline group, an oxazolidinone group, a carbodiimide group, a carbamide group, an amino group, and an aziridine group.

[0014] Examples of the compound having the functional group include an oxazolidinone group-containing compound obtained by reacting a blocked isocyanate compound with an epoxy compound, an oxazoline group-containing compound in which an oxazoline group has been introduced into the polymer main chain of an acrylic or styrene / acrylic copolymer, a carbodiimide group-containing compound (polyvalent carbodiimide) in which a carbodiimide group has been introduced into the molecule, a carbamide group-containing compound such as a urea derivative, an amino group-containing polymer in which an amino group has been introduced into the molecule, and an aziridine group-containing compound (2,2-bis(hydroxymethyl)butanol tris[3-(1-aziridinyl)propionate]) in which an aziridine group has been introduced into the molecular end. Among these, from the viewpoint of improving the adhesion between the surface-modified fiber and the rubber, an oxazolidinone group-containing compound obtained by reacting a blocked isocyanate compound with an epoxy compound is preferred, and from the viewpoint of reducing the environmental load, an oxazoline group-containing compound is preferred.

[0015] From the viewpoint of improving the adhesion to the rubber, the surface modification layer preferably covers the entire surface of the fiber, but it is sufficient that the surface modification layer substantially covers at least a part of the fiber surface. The specific amount of the surface modification layer covering the fiber surface is preferably 0.01 to 5.0 parts by mass, more preferably 0.05 to 1.0 parts by mass, and even more preferably 0.1 to 0.3 parts by mass, based on 100 parts by mass of the fiber used as the raw material.

[0016] <Textile> There is no particular restriction on the fibers used in the surface-modified fiber of the present invention, but it can be suitably used for hydrophobic fibers made of hydrophobic resins that could not be strongly adhered to rubber by conventional techniques. Hydrophobic fibers generally do not have polar functional groups on the fiber surface, so they have poor affinity with the adhesive components described below and cannot be strongly adhered to rubber. However, by providing a surface-modified layer on the fiber surface as in the present invention, even hydrophobic fibers can be strongly adhered to rubber. In the present invention, the term "fiber" includes not only single fibers and long fibers, but also nonwoven fabrics, woven fabrics, knitted fabrics, felts, sponges, and other forms.

[0017] Examples of hydrophobic fibers that can be used in the present invention include polyolefin fibers such as polyethylene and polypropylene, polyester fibers such as polyethylene terephthalate, and wholly aromatic polyester fibers. Among these, polyester fibers are preferred because they are excellent in terms of production cost, strength, heat resistance, durability, and the like.

[0018] In the present invention, hydrophilic fibers may be used. Examples of hydrophilic synthetic fibers include synthetic fibers made of a thermoplastic resin having hydrophilic functional groups such as hydroxyl groups, carboxyl groups, sulfonic acid groups, and amino groups, and / or hydrophilic bonds such as amide bonds. Specific examples of such thermoplastic resins include polyvinyl alcohol-based resins, polyamide-based resins (aliphatic polyamides such as polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 610, polyamide 612, and polyamide 9C (a polyamide composed of nonanediamine and cyclohexanedicarboxylic acid); semi-aromatic polyamides synthesized from aromatic dicarboxylic acids and aliphatic diamines, such as polyamide 9T (a polyamide composed of nonanediamine and terephthalic acid); wholly aromatic polyamides synthesized from aromatic dicarboxylic acids and aromatic diamines, such as polyparaphenylene terephthalamide), and polyacrylamide-based resins). Among these, polyvinyl alcohol-based resins and polyamide-based resins are preferred. The hydrophilic synthetic fibers may be used alone or in combination of two or more. In addition, these hydrophilic synthetic fibers may be further subjected to a hydrophilization treatment described below in order to further enhance the hydrophilicity.

[0019] Examples of hydrophilic natural fibers include natural cellulose fibers such as wood pulp, e.g., kraft pulp, and non-wood pulp, e.g., cotton pulp and straw pulp. Hydrophilic regenerated fibers include regenerated cellulosic fibers such as rayon, lyocell, cupra, and polynosic. These natural fibers and regenerated fibers may be used alone or in combination of two or more. Furthermore, these hydrophilic natural fibers and regenerated fibers may be further subjected to a hydrophilization treatment described later in order to further enhance the hydrophilicity.

[0020] The hydrophilic fiber may have at least a hydrophilic surface, and may be, for example, a hydrophobic fiber whose surface has been hydrophilized, or a core-sheath type composite fiber in which a hydrophobic resin is used as the core and a hydrophilic resin is used as the sheath. Examples of hydrophilic resins constituting the sheath are described in the description of hydrophilic synthetic fibers. Examples of hydrophobic fibers made of hydrophobic resins include the hydrophobic fibers described above.

[0021] The hydrophilization treatment is not particularly limited as long as it is a treatment that chemically or physically imparts hydrophilic functional groups to the fiber surface. For example, the hydrophilic treatment can be carried out by a method in which a hydrophobic fiber made of the hydrophobic resin is modified with a compound containing a hydrophilic functional group such as an isocyanate group, an epoxy group, a hydroxyl group, an amino group, an ether group, an aldehyde group, a carbonyl group, a carboxyl group, or a urethane group, or a derivative thereof, or by a method in which the surface is modified by electron beam irradiation.

[0022] As the hydrophilic fibers used in the present invention, from the viewpoint of being used as reinforcing fibers, synthetic fibers and regenerated fibers are preferred, and among them, one or more types of fibers selected from polyester-based fibers, polyamide-based fibers, polyvinyl alcohol-based fibers, and regenerated cellulose-based fibers are preferred. In the present invention, one type of fiber may be used alone, or two or more types may be used in combination.

[0023] <Method of manufacturing surface modified fiber> There is no particular limitation on the method for producing the surface-modified fiber of the present invention, but the fiber can be produced by a method in which a solution of the compound constituting the above-mentioned surface-modified layer in water or an organic solvent is prepared, the solution is applied to the fiber, and then the fiber is dried by heat treatment or the like. The method for applying the solution of the surface modifier to the fibers is not particularly limited, and is preferably carried out by one or more methods selected from, for example, immersion, roll coater, oiling roller, oiling guide, nozzle (spray) application, brush application, and the like.

[0024] The heat treatment for drying the solution is preferably carried out at a temperature of 100 to 250° C. for a treatment time of 0.1 seconds to 2 minutes. The heat treatment may be carried out only once at a specific temperature, or may be carried out two or more times by changing the treatment temperature and treatment time.

[0025] The surface modification layer may contain other components in addition to those described above, such as a crosslinking agent, an acid, a base, an inorganic salt, an organic salt, a pigment, a dye, an antioxidant, a polymerization initiator, and a plasticizer. When the surface modification layer contains the other components, the content of the other components in the surface modification layer is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, from the viewpoint of improving the adhesive strength with the rubber.

[0026] [Reinforcing fiber] The reinforcing fiber of the present invention has the surface-modified fiber of the present invention and an adhesive layer containing a conjugated diene rubber covering at least a part of the surface of the surface-modified fiber. In the present invention, since the affinity between the surface-modified fiber and the adhesive layer is high, it is possible to firmly bond the fiber to the adhesive layer and the adhesive layer to the rubber. The reinforcing fiber of the present invention may have the entire surface of the surface-modified fiber covered with an adhesive layer, but it is sufficient that at least a portion of the surface is covered with an adhesive layer, and for example, the adhesive component may be present as a film or layer.

[0027] In addition, the adhesive layer in the present invention can obtain a reinforcing fiber having excellent adhesion to rubber even if it does not contain formaldehyde or a resin made from formaldehyde, which is harmful to the human body. In the present invention, if the adhesive layer contains a resin made from formaldehyde, the resin may be, for example, a resorol / formaldehyde resin, a phenol / formaldehyde resin, a melamine / formaldehyde resin, or a derivative thereof. In the case where the adhesive layer contains the formaldehyde component, the content is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, particularly more preferably 1 part by mass or less, and particularly preferably substantially free, relative to 100 parts by mass of the conjugated diene rubber. The formaldehyde content can be measured by extracting the adhesive layer from the reinforcing fiber with a solvent such as toluene, and then using HPLC or the like.

[0028] <Adhesive layer> The adhesive layer in the reinforcing fiber of the present invention is not particularly limited as long as it contains a conjugated diene rubber, and can be formed, for example, by attaching an adhesive component consisting of a solution in which a conjugated diene rubber is dissolved in oil, or an adhesive component consisting of an emulsion in which a conjugated diene rubber is dispersed in water, to the surface-modified fiber. The following is a specific description of the embodiment of the adhesive layer.

[0029] [Conjugated diene rubber] The conjugated diene rubber used in the present invention contains at least a monomer unit derived from a conjugated diene in the molecule (hereinafter also referred to as a "conjugated diene unit"). For example, it is preferable that the conjugated diene rubber contains 50 mol % or more of monomer units derived from a conjugated diene among all monomer units in the conjugated diene rubber. Examples of the conjugated diene monomer include butadiene, 2-methyl-1,3-butadiene (hereinafter also referred to as "isoprene"), 2,3-dimethylbutadiene, 2-phenylbutadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, 1,3-octadiene, 1,3-cyclohexadiene, 2-methyl-1,3-octadiene, 1,3,7-octatriene, β-farnesene (hereinafter also referred to as "farnesene"), myrcene, and chloroprene. These conjugated dienes may be used alone or in combination of two or more. From the viewpoint of reactivity during vulcanization, it is more preferable that the conjugated diene rubber has a monomer unit derived from one or more selected from butadiene, isoprene, and farnesene.

[0030] The conjugated diene rubber used in the present invention may contain units derived from other monomers than the conjugated diene monomers, so long as the units do not impair adhesion. Examples of other monomers include copolymerizable ethylenically unsaturated monomers and aromatic vinyl compounds. Examples of the ethylenically unsaturated monomer include olefins such as ethylene, 1-butene, and isobutylene. Examples of the aromatic vinyl compound include styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 4-t-butylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2,4-dimethylstyrene, 2,4-diisopropylstyrene, 2,4,6-trimethylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, 1-vinylnaphthalene, 2-vinylnaphthalene, vinylanthracene, N,N-diethyl-4-aminoethylstyrene, vinylpyridine, 4-methoxystyrene, monochlorostyrene, dichlorostyrene, and divinylbenzene. These may be used alone or in combination of two or more. When the conjugated diene rubber contains monomer units derived from monomers other than the conjugated diene monomer, the content thereof is preferably 30 mol % or less, more preferably 10 mol % or less, and further preferably 5 mol % or less.

[0031] The conjugated diene rubber used in the present invention is preferably a modified conjugated diene rubber having a hydrogen-bonding functional group in a portion of the conjugated diene rubber, and more preferably a modified conjugated diene rubber containing a conjugated diene unit in at least a portion of the polymer chain and having a hydrogen-bonding functional group in a side chain or at an end of the polymer chain. When the modified conjugated diene rubber is used as the conjugated diene rubber, the modified conjugated diene rubber can bond the rubber and the surface-modified fiber, which are the adherends, by interacting with each other. When the modified conjugated diene rubber and the adherend rubber are vulcanized to form a covalent bond, a strong cohesive force is generated, and the adhesion is further improved. It is also believed that the hydrogen-bonding functional groups contained in the modified conjugated diene rubber form hydrogen bonds with the surface-modified layer of the surface-modified fiber, thereby improving adhesion.

[0032] In this specification, the term "hydrogen bond" refers to a bonding interaction formed between a hydrogen atom (donor) that is bonded to an atom with high electronegativity (O, N, S, etc.) and is electrically positively polarized, and an electronegative atom (acceptor) that has a lone pair of electrons.

[0033] In the present invention, the "hydrogen-bonding functional group" refers to a functional group that can function as a donor and an acceptor in the hydrogen bond. Specific examples of the functional group include a hydroxyl group, an epoxy group, an ether group, a mercapto group, a carboxyl group, a carbonyl group, an aldehyde group, an amino group, an imino group, an imidazole group, a urethane group, an amide group, a urea group, an isocyanate group, a nitrile group, a silanol group, and derivatives thereof. An example of the derivative of the aldehyde group is an acetalized product thereof. An example of the derivative of the carboxyl group is a salt thereof, an esterified product thereof, an amidated product thereof, or an acid anhydride thereof. An example of the derivative of the silanol group is an esterified product thereof. In addition, an example of the carboxyl group is a group derived from a monocarboxylic acid or a group derived from a dicarboxylic acid. Among these, one or more selected from a hydroxy group, an epoxy group, an aldehyde group, an acetalized product of an aldehyde group, a carboxy group, a salt of a carboxy group, an esterified product of a carboxy group, an acid anhydride of a carboxy group, a silanol group, an esterified product of a silanol group, an amino group, an imidazole group, and a mercapto group are preferable. Among these, from the viewpoint of improving adhesion and ease of production of the conjugated diene rubber, one or more selected from a hydroxy group, a carboxy group, a carbonyl group, a salt of a carboxy group, an esterified product of a carboxy group, and an acid anhydride of a carboxy group are preferred, one or more selected from a carboxy group, an esterified product of a carboxy group, and an acid anhydride of a carboxy group are more preferred, and an esterified product of maleic anhydride and a functional group derived from maleic anhydride are even more preferred.

[0034] From the viewpoint of obtaining a reinforcing fiber having excellent rubber adhesion, the number of hydrogen-bonding functional groups in the modified conjugated diene rubber is, on average, preferably 1 or more, more preferably 3 or more, and even more preferably 4 or more per molecule. Moreover, from the viewpoint of controlling the viscosity of the modified conjugated diene rubber within an appropriate range and improving handleability, the number of hydrogen-bonding functional groups is, on average, preferably 80 or less, more preferably 40 or less, even more preferably 30 or less, still more preferably 20 or less, and even more preferably 15 or less per molecule.

[0035] The average number of hydrogen-bonding functional groups per molecule of the modified conjugated diene rubber is calculated from the equivalent weight (g / eq) of the hydrogen-bonding functional groups of the modified conjugated diene rubber and the number-average molecular weight Mn in terms of styrene, based on the following formula: The equivalent weight of the hydrogen-bonding functional groups of the modified conjugated diene rubber means the mass of the conjugated diene bonded to each hydrogen-bonding functional group and the mass of other monomers other than the conjugated diene that are included as necessary. Average number of hydrogen-bonding functional groups per molecule = [(number average molecular weight (Mn)) / (molecular weight of styrene unit) x (average molecular weight of conjugated diene and other monomer units other than conjugated diene contained as necessary)] / (equivalent weight of hydrogen-bonding functional group) The method for calculating the equivalent weight of the hydrogen-bonding functional group can be appropriately selected depending on the type of the hydrogen-bonding functional group.

[0036] Examples of methods for obtaining modified conjugated diene rubber include a method of adding a modifying compound to a polymerized product of a conjugated diene monomer (hereinafter also referred to as "production method (1)"); a method of obtaining the modified conjugated diene polymer by oxidizing the conjugated diene polymer (hereinafter also referred to as "production method (2)"); a method of obtaining the modified conjugated diene monomer by copolymerizing the conjugated diene monomer with a radical polymerizable compound having a hydrogen bond functional group (hereinafter also referred to as "production method (3)"); and a method of adding a modifying compound capable of reacting with the polymerization active terminal to a polymerized product of an unmodified conjugated diene monomer having a polymerization active terminal before adding a polymerization terminator (hereinafter also referred to as "production method (4)"). Among these, from the viewpoint of productivity, production is preferably performed by production method (1) or (2) or (3), more preferably by production method (1) or (3), and even more preferably by production method (1).

[0037] [Production method of modified conjugated diene rubber (1)] The production method (1) is a method in which a modifying compound is added to a polymer of a conjugated diene monomer, that is, an unmodified conjugated diene rubber (hereinafter also referred to as "unmodified conjugated diene rubber"). The unmodified conjugated diene rubber can be obtained by polymerizing a conjugated diene and, if necessary, a monomer other than the conjugated diene, for example, by emulsion polymerization or solution polymerization.

[0038] As the solution polymerization method, a known method or a method similar to a known method can be applied. For example, a predetermined amount of a monomer containing a conjugated diene is polymerized in a solvent using a Ziegler catalyst, a metallocene catalyst, or an anionically polymerizable active metal or active metal compound, if necessary in the presence of a polar compound. Examples of the solvent include aliphatic hydrocarbons such as n-butane, n-pentane, isopentane, n-hexane, n-heptane, and isooctane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; and aromatic hydrocarbons such as benzene, toluene, and xylene.

[0039] Examples of the anionically polymerizable active metal include alkali metals such as lithium, sodium, potassium, etc., alkaline earth metals such as beryllium, magnesium, calcium, strontium, barium, etc., lanthanoid rare earth metals such as lanthanum, neodymium, etc. Among these anionically polymerizable active metals, alkali metals and alkaline earth metals are preferred, and alkali metals are more preferred. As the anionically polymerizable active metal compound, organic alkali metal compounds are preferred.As organic alkali metal compounds, for example, organic monolithium compounds such as methyl lithium, ethyl lithium, n-butyl lithium, sec-butyl lithium, t-butyl lithium, hexyl lithium, phenyl lithium, stilbene lithium, etc.; polyfunctional organic lithium compounds such as dilithiomethane, dilithionaphthalene, 1,4-dilithiobutane, 1,4-dilithio-2-ethylcyclohexane, 1,3,5-trilithiobenzene, etc.; sodium naphthalene, potassium naphthalene, etc. are included.Among these organic alkali metal compounds, organic lithium compounds are preferred, and organic monolithium compounds are more preferred.

[0040] The amount of the organic alkali metal compound used can be appropriately set depending on the melt viscosity, molecular weight, etc. of the target unmodified conjugated diene rubber and modified conjugated diene rubber, but it is usually used in an amount of 0.01 to 3 parts by mass per 100 parts by mass of all monomers including conjugated diene. The above organic alkali metal compounds can also be reacted with secondary amines such as dibutylamine, dihexylamine, dibenzylamine, etc. to form organic alkali metal amides.

[0041] In anionic polymerization, polar compounds are usually used to adjust the microstructure of the conjugated diene moiety without deactivating the reaction. Examples of polar compounds include ether compounds such as dibutyl ether, tetrahydrofuran, ethylene glycol diethyl ether, and 2,2-di(2-tetrahydrofuryl)propane; tertiary amines such as tetramethylethylenediamine and trimethylamine; alkali metal alkoxides, and phosphine compounds. The polar compounds are usually used in an amount of 0.01 to 1000 mol relative to the organic alkali metal compound. The temperature for the solution polymerization is usually in the range of −80 to 150° C., preferably in the range of 0 to 100° C., and more preferably in the range of 10 to 90° C. The polymerization mode may be either a batch system or a continuous system. The polymerization reaction can be terminated by adding a polymerization terminator. Examples of the polymerization terminator include alcohols such as methanol and isopropanol. The resulting polymerization reaction liquid is poured into a poor solvent such as methanol to precipitate the polymerized product, or the polymerization reaction liquid is washed with water, separated, and then dried to isolate the unmodified conjugated diene rubber. Of the above methods, the solution polymerization method is preferred as the method for producing the unmodified conjugated diene rubber.

[0042] The emulsion polymerization method may be a known method or a method similar to a known method, for example, a monomer containing a predetermined amount of conjugated diene is emulsified and dispersed in the presence of an emulsifier, and emulsion-polymerized by a radical polymerization initiator. Examples of the emulsifier include salts of long-chain fatty acids having 10 or more carbon atoms, rosin acid salts, etc. Examples of the long-chain fatty acid salts include potassium salts or sodium salts of fatty acids such as capric acid, lauric acid, myristic acid, palmitic acid, oleic acid, and stearic acid. As the dispersion solvent, water is usually used, and it may contain a water-soluble organic solvent such as methanol or ethanol within a range that does not impair the stability during polymerization. Examples of the radical polymerization initiator include persulfates such as ammonium persulfate and potassium persulfate, organic peroxides, and hydrogen peroxide. A chain transfer agent may be used to adjust the molecular weight of the resulting unmodified conjugated diene rubber. Examples of the chain transfer agent include mercaptans such as t-dodecyl mercaptan and n-dodecyl mercaptan; carbon tetrachloride, thioglycolic acid, diterpene, terpinolene, γ-terpinene, and α-methylstyrene dimer.

[0043] The temperature of the emulsion polymerization can be appropriately set depending on the type of radical polymerization initiator used, etc., but is usually in the range of 0 to 100° C., preferably in the range of 0 to 60° C. The polymerization mode may be either continuous polymerization or batch polymerization.

[0044] The polymerization reaction can be terminated by adding a polymerization terminator, such as an amine compound such as isopropylhydroxylamine, diethylhydroxylamine, or hydroxylamine, a quinone compound such as hydroquinone or benzoquinone, or sodium nitrite.

[0045] After the polymerization reaction is stopped, an antioxidant may be added as necessary. After the polymerization reaction is stopped, unreacted monomers are removed from the obtained latex as necessary, and then the polymerized product is coagulated using salts such as sodium chloride, calcium chloride, and potassium chloride as a coagulant, and an acid such as nitric acid or sulfuric acid is added as necessary to adjust the pH of the coagulation system to a predetermined value, and then the dispersion solvent is separated to recover the polymerized product. Next, the polymerized product is washed with water, dehydrated, and dried to obtain an unmodified conjugated diene rubber. During the coagulation, the latex and an extender oil that has been previously made into an emulsified dispersion may be mixed as necessary, and the product may be recovered as an oil-extended unmodified conjugated diene rubber.

[0046] (Modifying compound used in production method (1)) The modified compound used in the manufacturing method (1) is not particularly limited, but from the viewpoint of improving the adhesiveness of the reinforcing fiber, it is preferable to use a compound having a hydrogen-bonding functional group. Examples of the hydrogen-bonding functional group include the same as those described above. Among them, from the viewpoint of the strength of the hydrogen bond force, an amino group, an imidazole group, a urea group, a hydroxyl group, an epoxy group, a mercapto group, a silanol group, an aldehyde group, a carboxyl group, and a derivative thereof are preferable. As a derivative of a carboxyl group, a salt thereof, an ester thereof, an amidation thereof, or an acid anhydride thereof is preferable. These modified compounds having a hydrogen-bonding functional group may be used alone or in combination of two or more kinds.

[0047] Examples of the modifying compound include unsaturated carboxylic acids such as maleic acid, fumaric acid, citraconic acid, and itaconic acid; unsaturated carboxylic anhydrides such as maleic anhydride, citraconic anhydride, 2,3-dimethylmaleic anhydride, and itaconic anhydride; unsaturated carboxylic esters such as maleic acid esters, fumaric acid esters, citraconic acid esters, and itaconic acid esters; unsaturated carboxylic amides such as maleic acid amides, fumaric acid amides, citraconic acid amides, and itaconic acid amides; unsaturated carboxylic imides such as maleic acid imides, fumaric acid imides, citraconic acid imides, and itaconic acid imides; vinyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, mercaptomethylmethyldimethoxysilane, ... Examples of silane compounds include ethoxysilane, mercaptomethyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, 2-mercaptoethylmethoxydimethylsilane, 2-mercaptoethylethoxydimethylsilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyldimethoxymethylsilane, 3-mercaptopropyldiethoxymethylsilane, 3-mercaptopropyldimethoxyethylsilane, 3-mercaptopropyldiethoxyethylsilane, 3-mercaptopropylmethoxydimethylsilane, and 3-mercaptopropylethoxydimethylsilane.

[0048] The amount of the modifying compound used is preferably 0.1 to 100 parts by mass, more preferably 0.5 to 50 parts by mass, and further preferably 1 to 30 parts by mass, based on 100 parts by mass of the unmodified conjugated diene rubber. The reaction temperature is usually preferably in the range of 0 to 200°C, more preferably in the range of 50 to 200°C. Alternatively, the unmodified conjugated diene rubber may be grafted with the modifying compound to introduce a hydrogen-bonding functional group, and then a modifying compound capable of reacting with the functional group may be added to introduce another hydrogen-bonding functional group into the polymer.Specifically, for example, a method may be used in which maleic anhydride is grafted onto an unmodified conjugated diene rubber obtained by living anionic polymerization, and then a compound having a hydroxyl group, such as 2-hydroxyethyl methacrylate or methanol, or a compound such as water is reacted therewith.

[0049] The amount of the modified compound added to the modified conjugated diene rubber is preferably 0.5 to 40 parts by mass, more preferably 1 to 30 parts by mass, and even more preferably 1.5 to 20 parts by mass, based on 100 parts by mass of the unmodified conjugated diene rubber. The amount of the modified compound added to the modified conjugated diene rubber can be calculated based on the acid value of the modified compound, or can be determined using various analytical instruments such as infrared spectroscopy and nuclear magnetic resonance spectroscopy.

[0050] The method of adding the modifying compound to the unmodified conjugated diene rubber is not particularly limited, and examples thereof include a method of adding a liquid unmodified conjugated diene rubber, one or more modifying compounds selected from unsaturated carboxylic acids, unsaturated carboxylic acid derivatives, silane compounds, etc., and further adding a radical generator as necessary, and heating the resulting mixture in the presence or absence of an organic solvent. There is no particular limit to the radical generator used, and commercially available organic peroxides, azo compounds, hydrogen peroxide, etc. can be used. The organic solvent used in the above method generally includes hydrocarbon solvents and halogenated hydrocarbon solvents. Among these organic solvents, hydrocarbon solvents such as n-butane, n-hexane, n-heptane, cyclohexane, benzene, toluene, and xylene are preferred.

[0051] Furthermore, when the reaction of adding the modified compound is carried out by the above method, an antioxidant may be added from the viewpoint of suppressing side reactions, etc. The antioxidant can be a commercially available one, such as butylated hydroxytoluene (BHT), N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (Nocrac 6C), etc. The amount of the antioxidant added is preferably 0.01 to 10 parts by mass, and more preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the unmodified conjugated diene rubber. When the amount of the antioxidant added is within the above range, side reactions can be suppressed, and the modified conjugated diene rubber can be obtained in good yield.

[0052] [Physical Properties of Conjugated Diene Rubber] The weight average molecular weight (Mw) of the conjugated diene rubber is not particularly limited, but from the viewpoint of improving adhesion, it is preferably more than 2,000, more preferably 5,000 or more, even more preferably 10,000 or more, even more preferably 15,000 or more, even more preferably 20,000 or more, and particularly preferably 25,000 or more, and from the viewpoint of handleability, it is preferably 120,000 or less, more preferably 100,000 or less, even more preferably 75,000 or less, and even more preferably 55,000 or less.

[0053] The number average molecular weight (Mn) of the conjugated diene rubber is not particularly limited, but from the viewpoint of improving adhesion, it is preferably 2,000 or more, more preferably 5,000 or more, even more preferably 10,000 or more, even more preferably 15,000 or more, even more preferably 20,000 or more, and particularly preferably 25,000 or more, and from the viewpoint of handleability, it is preferably 120,000 or less, more preferably 75,000 or less, even more preferably 50,000 or less, and even more preferably 47,000 or less. The Mw and Mn of the conjugated diene rubber are the weight average molecular weight and number average molecular weight in terms of polystyrene determined by gel permeation chromatography (GPC), and specifically can be measured by the method described in the examples.

[0054] The molecular weight distribution (Mw / Mn) of the conjugated diene rubber is preferably 1.00 to 5.00, more preferably 1.00 to 3.00, even more preferably 1.00 to 2.00, even more preferably 1.00 to 1.50, and particularly preferably 1.00 to 1.30. When Mw / Mn is within the above range, the viscosity of the conjugated diene rubber varies little, making it easy to handle. The molecular weight distribution (Mw / Mn) means the ratio of weight average molecular weight (Mw) / number average molecular weight (Mn) calculated in terms of standard polystyrene, determined by GPC measurement.

[0055] From the viewpoint of adhesion between the conjugated diene rubber and the fibers, the conjugated diene rubber is preferably in a liquid state. In this specification, "liquid" means that the melt viscosity of the conjugated diene rubber measured at 38°C is 4,000 Pa·s or less. From the viewpoint of improving adhesiveness, the melt viscosity is preferably 0.1 Pa·s or more, more preferably 1 Pa·s or more, even more preferably 10 Pa·s or more, even more preferably 30 Pa·s or more, and even more preferably 50 Pa·s or more, and from the viewpoint of handleability, it is preferably 2,500 Pa·s or less, more preferably 2,100 Pa·s or less. When the melt viscosity is within the above range, the adhesiveness of the conjugated diene rubber can be improved while improving the handleability. The melt viscosity of the conjugated diene rubber means a viscosity measured at 38° C. using a Brookfield viscometer (B-type viscometer).

[0056] The glass transition temperature (Tg) of the conjugated diene rubber may vary depending on the vinyl content of the conjugated diene unit, the type of conjugated diene, the content of units derived from monomers other than the conjugated diene, etc., but is preferably −100 to 10° C., more preferably −100 to 0° C., and even more preferably −100 to −10° C. When Tg is within the above range, high viscosity can be suppressed, making the rubber easy to handle.

[0057] The vinyl content of the conjugated diene rubber is preferably 80 mol % or less, more preferably 50 mol % or less, and even more preferably 30 mol % or less. When the vinyl content is within the above range, the adhesiveness is improved. In this specification, the term "vinyl content" refers to the total mol% of conjugated diene units bonded via 1,2-bonds or 3,4-bonds (conjugated diene units bonded via bonds other than 1,4-bonds) out of a total of 100 mol% of conjugated diene units contained in the modified liquid diene rubber. 1 It can be calculated from the integral ratio of a signal derived from a conjugated diene unit bonded via a 1,2-bond or a 3,4-bond to a signal derived from a conjugated diene unit bonded via a 1,4-bond, using H-NMR.

[0058] 〔oil〕 The adhesive layer in the present invention can be formed, for example, by applying an adhesive component consisting of a solution in which a conjugated diene rubber is dissolved in oil to the surface-modified fiber. In the present invention, it is preferable to use a so-called non-volatile oil, for example, having a vapor pressure of 10 Pa or less at 20°C. By using such an oil, the oil does not volatilize for a long period of time even after the adhesive component is applied to the surface of the fiber, so that coating unevenness of the adhesive component is unlikely to occur, and adhesion is improved. In addition, contamination of the manufacturing equipment during production can be suppressed. From these viewpoints, the oil has a vapor pressure of 8 Pa or less at 20°C, preferably 5 Pa or less, more preferably 1 Pa or less, even more preferably 0.1 Pa or less, and even more preferably 0.01 Pa or less. In the present invention, the vapor pressure of oil at 20° C. refers to a value calculated from the best fit curve obtained by applying the Antoine equation to the measured value measured by the gas flow method. When oil is used in the present invention, a heating step for resinification is not required, as compared with the conventional technology using RFL, and further, an evaporation step for removing water, etc. is not required, as compared with the conventional technology using a solvent such as water as a diluent. Therefore, compared with the conventional technology, efficient production is possible with simple equipment, and it is also environmentally friendly.

[0059] The oil having a vapor pressure of 10 Pa or less at 20° C. that can be used in the present invention is not particularly limited as long as it is compatible with the conjugated diene rubber, and examples of the oil include natural oils and synthetic oils. Examples of the natural oil include mineral oils and vegetable oils. Examples of mineral oils include paraffinic mineral oils, aromatic mineral oils, and naphthenic mineral oils obtained by conventional refining methods such as solvent refining and hydrogenation refining, as well as wax produced by the Fischer-Tropsch process (gas-to-liquid wax) and mineral oils produced by isomerizing wax. Commercially available paraffinic mineral oils include the "Diana Process Oil" series manufactured by Idemitsu Kosan Co., Ltd. and the "Super Oil" series manufactured by JX Nippon Oil & Energy Corporation. Examples of vegetable oils include linseed oil, camellia oil, macadamia nut oil, corn oil, mink oil, olive oil, avocado oil, camellia oil, castor oil, safflower oil, jojoba oil, sunflower oil, almond oil, rapeseed oil, sesame oil, soybean oil, peanut oil, cottonseed oil, coconut oil, palm kernel oil, and rice bran oil. Examples of synthetic oils include hydrocarbon synthetic oils, ester synthetic oils, and ether synthetic oils. Examples of hydrocarbon synthetic oils include α-olefin oligomers such as polybutene, polyisobutylene, 1-octene oligomers, 1-decene oligomers, and ethylene-propylene copolymers, or hydrogenated products thereof, alkylbenzenes, and alkylnaphthalenes. Examples of ester synthetic oils include triglycerin fatty esters, diglycerin fatty acid esters, monoglycerin fatty acid esters, monoalcohol fatty acid esters, and polyhydric alcohol fatty acid esters. Examples of ether synthetic oils include polyoxyalkylene glycols and polyphenyl ethers. Examples of commercially available synthetic oils include the "Linearene" series manufactured by Idemitsu Kosan Co., Ltd., and "FGC32", "FGC46", and "FGC68" manufactured by ANDEROL.

[0060] The oil may be one selected from the above natural oils and synthetic oils, or a mixture of two or more natural oils, two or more synthetic oils, or one or more natural oils and one or more synthetic oils. In the present invention, from the viewpoint of setting the viscosity of the adhesive component in an appropriate range and improving workability, mineral oils are preferred, and at least one selected from paraffinic mineral oils and naphthenic mineral oils are more preferred.

[0061] The flash point of the oil used in the present invention is preferably 70° C. or higher from the viewpoint of safety. From this viewpoint, the flash point of the oil is more preferably 100° C. or higher, even more preferably 130° C. or higher, and even more preferably 140° C. or higher. There is no particular upper limit to the flash point of the oil, but it is preferably 320° C. or lower.

[0062] From the viewpoint of improving adhesive strength with rubber, the content of the conjugated diene rubber in the adhesive component is preferably 1% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more, and is preferably 80% by mass or less, more preferably 60% by mass or less, even more preferably 50% by mass or less, and even more preferably 40% by mass or less. When the content of the conjugated diene rubber in the adhesive component is within the above range, sufficient adhesive strength can be obtained while preventing the viscosity of the adhesive component from becoming extremely high. In addition, the oil content in the adhesive component is preferably 20% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, still more preferably 60% by mass or more, and is preferably 99% by mass or less, more preferably 95% by mass or less, even more preferably 90% by mass or less.

[0063] The mass ratio of the conjugated diene rubber to the oil in the adhesive component [conjugated diene rubber (R):oil (O)] is preferably 0.1:9.9 to 8:2, more preferably 0.5:9.5 to 6:4, even more preferably 1:9 to 5:5, and even more preferably 1:9 to 4:6. It is generally known that oil deteriorates the adhesiveness of rubber, but when the conjugated diene rubber and the oil are mixed at the specific mass ratio, it is possible to lower the viscosity while maintaining the adhesiveness, improving the handleability of the adhesive component and the workability of attachment to the surface-modified fiber.

[0064] In the present invention, the adhesive layer may be formed by adhering an adhesive component comprising an emulsion of the conjugated diene rubber dispersed in water to the surface-modified fiber. When the conjugated diene rubber is dispersed in water to be used as an oil-in-water emulsion, it is preferable to prepare an emulsion (latex) of the adhesive component in advance by a mechanical or chemical method, and use it at a predetermined concentration by dilution or the like. Examples of mechanical methods include methods using a homogenizer, a homomixer, a disperser mixer, a colloid mill, a pipeline mixer, a high-pressure homogenizer, an ultrasonic emulsifier, etc., which can be used alone or in combination. As the chemical method, various methods such as inversion emulsification method, D phase emulsification method, HLB temperature emulsification method, gel emulsification method, and liquid crystal emulsification method can be mentioned, and inversion emulsification method is preferred from the viewpoint of easily obtaining an emulsion with a fine particle size. In addition, in order to obtain an emulsion with a fine particle size, it may be preferable to carry out the operation while heating at an appropriate temperature (e.g., 30 to 80°C) in order to reduce the viscosity of the modified conjugated diene rubber.

[0065] When the adhesive component is an emulsion, the content of the conjugated diene rubber in the adhesive component is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more, from the viewpoint of improving the adhesive strength with the rubber, and is preferably 60% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, and even more preferably 20% by mass or less. When the content of the conjugated diene rubber in the adhesive component is within the above range, it is possible to prevent the viscosity of the adhesive component from becoming extremely high while obtaining sufficient adhesive strength.

[0066] The conjugated diene rubber may be used alone or in combination of two or more kinds thereof. The oil may be used alone or in combination of two or more kinds thereof.

[0067] Furthermore, the adhesive component in the present invention may contain other components in addition to the conjugated diene rubber and oil, as long as the adhesive strength with the rubber is not impaired. Examples of the other components include other polymers (for example, unmodified conjugated diene rubbers), acids, alkalis, antioxidants, curing agents, dispersants, pigments, dyes, adhesion aids, and carbon black. When the adhesive component contains other components, the content thereof is preferably 10,000 parts by mass or less, more preferably 1,000 parts by mass or less, even more preferably 100 parts by mass or less, still more preferably 50 parts by mass or less, still more preferably 25 parts by mass or less, and still more preferably 10 parts by mass or less, relative to 100 parts by mass of the conjugated diene rubber.

[0068] [Method of manufacturing reinforcing fibers] The method for producing the reinforcing fiber of the present invention is not particularly limited, and the fiber can be produced by a method including a step of adhering the conjugated diene rubber in a mixed state with the oil to a fiber, or a step of adhering the conjugated diene rubber in a dispersed state in water to a fiber. In the present invention, from the viewpoint of efficiently adhering the conjugated diene rubber to the surface-modified fiber and from the viewpoint of suppressing contamination of the production equipment, a method including a step of adhering the conjugated diene rubber to the fiber in a mixed state with the oil is preferred. More specifically, the method for producing the reinforcing fiber of the present invention is as follows.

[0069] [Method (I)] There are no particular limitations on method (I) as long as it is a method for forming an adhesive layer made of the adhesive component on the surface of the surface-modified fiber, but from the viewpoint of improving adhesion to rubber, a method including the following step I-1 is preferred. Step I-1: A step of attaching the adhesive component to the surface of the surface-modified fiber

[0070] In step I-1, the method for attaching the adhesive component to the surface-modified fiber is not particularly limited, and examples thereof include a method in which the adhesive component is attached as is, a method in which a solvent is added to the adhesive component as necessary, and the like. The adhesive component is preferably applied by one or more methods selected from immersion, roll coater, oiling roller, oiling guide, nozzle (spray) application, brush application, and the like.

[0071] From the viewpoint of improving adhesion between the reinforcing fibers and the rubber, the amount of the adhesive component attached is preferably 0.01 part by mass or more, more preferably 0.1 part by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the fibers used as the raw material, and from the viewpoint of balancing production cost and effect, it is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less.

[0072] In the present invention, when a conjugated diene rubber and a specific oil are used in combination, the reinforcing fiber of the present invention can be obtained by adhering an adhesive component to the surface-modified fiber and then allowing it to settle at room temperature of about 20°C for about 3 to 10 days, but in some cases, the following step I-2 may be carried out. Step I-2: A step of heat treating the surface-modified fiber having the adhesive component attached thereto obtained in step I-1. The heat treatment in step I-2 is preferably carried out at a treatment temperature of 100 to 200° C. for a treatment time of 0.1 seconds to 2 minutes. Since the conjugated diene rubber contained in the adhesive component has reactive multiple bonds, the heat treatment in the presence of oxygen is preferably carried out at 200° C. or less, and more preferably at 175° C. or less. When the heat treatment temperature is within the above range, the amount of reactive multiple bonds in the conjugated diene rubber is not reduced, and the adhesive strength can be improved, fiber deterioration is suppressed, and quality such as coloring is also improved.

[0073] The reinforcing fiber may contain other components in addition to the surface-modified fiber and the adhesive component, such as a crosslinking agent, an acid, a base, an inorganic salt, an organic salt, a pigment, a dye, an antioxidant, a polymerization initiator, and a plasticizer. The total content of the hydrophilic fibers and the adhesive component in the reinforcing fibers is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, from the viewpoint of improving adhesive strength with rubber and reinforcing strength.

[0074] <Properties of reinforcing fibers> The reinforcing fiber is preferably a multifilament having a single yarn fineness of 0.1 dtex or more and 30 dtex or less. The single yarn fineness may be less than 0.1 dtex, but is preferably 0.1 dtex or more since it is difficult to produce industrially. Furthermore, if the single yarn fineness is 30 dtex or less, the surface area of ​​the fiber when used as a reinforcing fiber is large, thereby improving adhesion to rubber. From this viewpoint, the reinforcing fiber of the present invention is preferably a multifilament having a single yarn fineness of more preferably 0.3 dtex or more, even more preferably 0.5 dtex or more, even more preferably 1 dtex or more, and more preferably 20 dtex or less, even more preferably 15 dtex or less, and even more preferably 10 dtex or less.

[0075] The rubber adhesive strength of the reinforcing fiber of the present invention is preferably 30N / 25.4mm or more, more preferably 50N / 25.4mm or more, even more preferably 70N / 25.4mm or more, even more preferably 80N / 25.4mm or more, and usually 200N / 25.4mm or less. When the rubber adhesive strength of the reinforcing fiber is the lower limit or more, a woven fabric, knitted fabric, and molded article having excellent reinforcing strength can be obtained. The rubber adhesive strength of the reinforcing fiber of the present invention is preferably 30 N / 3 or more, more preferably 40 N / 3 or more, even more preferably 50 N / 3 or more, and even more preferably 60 N / 3 or more, and is usually 200 N / 3 or less. When the rubber adhesive strength of the reinforcing fiber is equal to or more than the lower limit, a woven fabric, knitted fabric, and molded article having excellent reinforcing strength can be obtained. The adhesive strength of the reinforcing fiber to rubber can be measured by the method described in the Examples.

[0076] The reinforcing fiber of the present invention can be used in any shape, but is preferably used in the form of a fiber cord, woven fabric, knitted fabric, etc., which contains the reinforcing fiber at least in part, and is more preferably used as a woven fabric or knitted fabric which contains the reinforcing fiber at least in part. For example, it can be used as a knitted fabric to be bonded to rubber, as described later. It can also be used as a reinforcing fiber to be embedded in resin, cement, etc.

[0077] [Molded body] The molded article of the present invention is not particularly limited as long as it uses the reinforcing fiber. Among them, since the reinforcing fiber has excellent adhesion to rubber, a molded article having the reinforcing fiber and a rubber layer (hereinafter also referred to as a "rubber molded article") is particularly preferred. From the viewpoint of maintaining the shape of the rubber, the reinforcing fiber used in the rubber molded article is preferably used as a woven or knitted fabric containing the reinforcing fiber at least in part, and more preferably used as a laminate in which a reinforcing layer made of a woven or knitted fabric containing the reinforcing fiber at least in part is laminated with a rubber layer. A preferred embodiment of the molded body of the present invention is a molded body having a fiber, a surface modification layer, an adhesive layer, and a rubber layer in this order, and the adhesive strength between the adhesive layer and the rubber layer is preferably 70 N or more per 25.4 mm width, more preferably 80 N or more. If the adhesive strength is 70 N or more, the molded body can be suitably used for various applications described below.

[0078] The rubber molded article can be used as a component of rubber products such as tires, e.g., automobile tires, belts, e.g., conveyor belts, timing belts, hoses, and vibration-proof rubber, and among these, it is more preferable to use the rubber molded article as a tire, a belt, or a hose. In the case of automobile tires, the tire can be used in various components, such as belts, carcass plies, breakers, bead tapes, etc., which are made of composite materials of reinforcing fibers and rubber components. The hose can be used for the purpose of transporting various fluids in various applications, and is suitable, for example, as a hose for transporting fluids in automobiles. In particular, it is preferable to use the hose as a hose for liquid fuels in automobiles, a brake oil hose, and a hose for refrigerants in automobiles, and it is more preferable to use the hose as a brake oil hose in automobiles.

[0079] The rubber molded article is preferably molded using the reinforcing fibers and a rubber composition obtained by compounding a rubber component with compounding agents usually used in the rubber industry. The rubber component is not particularly limited, and examples thereof include NR (natural rubber), IR (polyisoprene rubber), BR (polybutadiene rubber), SBR (styrene-butadiene rubber), NBR (nitrile rubber), EPM (ethylene-propylene copolymer rubber), EPDM (ethylene-propylene-non-conjugated diene copolymer rubber), IIR (butyl rubber), halogenated butyl rubber, and CR (chloroprene rubber). Among these, it is preferable to use NR, IR, BR, SBR, EPDM, and CR, and it is more preferable to use EPDM. These rubber components may be used alone or in combination of two or more. For tire applications, those generally used in the tire industry can be used. Among these, it is preferable to use natural rubber alone or in combination with SBR. When natural rubber and SBR are combined, from the viewpoint of suppressing the deterioration of physical properties due to reversion of rubber, it is preferable that the mass ratio of natural rubber to SBR (natural rubber / SBR) is in the range of 50 / 50 to 90 / 10.

[0080] Examples of the natural rubber include natural rubber commonly used in the tire industry, such as TSR (Technically Specified Rubber) including SMR (Malaysian TSR), SIR (Indonesian TSR), and STR (Thailand TSR), and RSS (Ribbed Smoked Sheet); highly purified natural rubber, modified natural rubber including epoxidized natural rubber, hydroxylated natural rubber, hydrogenated natural rubber, and grafted natural rubber.

[0081] The SBR may be any of those commonly used in tires, but more specifically, the styrene content is preferably 0.1 to 70% by mass, more preferably 5 to 50% by mass, and even more preferably 15 to 35% by mass, and the vinyl content is preferably 0.1 to 60% by mass, and more preferably 0.1 to 55% by mass. The weight average molecular weight (Mw) of the SBR is preferably 100,000 to 2,500,000, more preferably 150,000 to 2,000,000, and even more preferably 200,000 to 1,500,000. Within the above range, both processability and mechanical strength can be achieved. The weight average molecular weight of the SBR is the weight average molecular weight calculated in terms of polystyrene and determined by gel permeation chromatography (GPC). The SBR may be modified SBR in which a functional group has been introduced into SBR, as long as the effect of the present invention is not impaired. Examples of the functional group include an amino group, an alkoxysilyl group, a hydroxy group, an epoxy group, and a carboxy group.

[0082] The rubber composition may further contain a filler in addition to the rubber component. Examples of the filler include inorganic fillers such as carbon black, silica, clay, mica, calcium carbonate, magnesium hydroxide, aluminum hydroxide, barium sulfate, titanium oxide, glass fiber, fibrous filler, and glass balloons; and organic fillers such as resin particles, wood powder, and cork powder. By including such a filler in the rubber composition, it is possible to improve physical properties such as mechanical strength, heat resistance, and weather resistance, adjust hardness, and increase the amount of rubber. From the viewpoint of improving physical properties such as mechanical strength, carbon black and silica are preferred among the above fillers.

[0083] Examples of the carbon black include furnace black, channel black, thermal black, acetylene black, and ketjen black. Among these carbon blacks, furnace black is preferred from the viewpoint of improving the crosslinking rate and mechanical strength. The average particle size of the carbon black is preferably 5 to 100 nm, more preferably 5 to 80 nm, and further preferably 5 to 70 nm. The average particle size of the carbon black can be determined by measuring the diameter of the particles using a transmission electron microscope and calculating the average value.

[0084] Examples of the silica include wet silica (hydrated silicic acid), dry silica (anhydrous silicic acid), calcium silicate, aluminum silicate, etc. Among these silicas, wet silica is preferred. The average particle size of the silica is preferably from 0.5 to 200 nm, more preferably from 5 to 150 nm, and even more preferably from 10 to 100 nm. The average particle size of the silica can be determined by measuring the diameter of the particles using a transmission electron microscope and calculating the average value.

[0085] In the rubber composition, the amount of the filler per 100 parts by mass of the rubber component is preferably 20 to 150 parts by mass, more preferably 25 to 130 parts by mass, and further preferably 25 to 110 parts by mass. When a filler other than silica and carbon black is used as the filler, the content thereof is preferably 20 to 120 parts by mass, more preferably 20 to 90 parts by mass, and further preferably 20 to 80 parts by mass, based on 100 parts by mass of the rubber component. These fillers may be used alone or in combination of two or more.

[0086] The rubber composition may further contain a crosslinking agent to crosslink the rubber component. Examples of the crosslinking agent include sulfur, sulfur compounds, oxygen, organic peroxides, phenolic resins, amino resins, quinone and quinone dioxime derivatives, halogen compounds, aldehyde compounds, alcohol compounds, epoxy compounds, metal halides and organometallic halides, and silane compounds. These crosslinking agents may be used alone or in combination of two or more. From the viewpoint of the mechanical properties of the crosslinked product, the crosslinking agent is contained in an amount of usually 0.1 to 10 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 0.8 to 5 parts by mass, per 100 parts by mass of the rubber component.

[0087] The rubber composition may further contain a vulcanization accelerator when sulfur, a sulfur compound, etc. are contained as a crosslinking agent for crosslinking (vulcanizing) the rubber component. Examples of the vulcanization accelerator include guanidine-based compounds, sulfenamide-based compounds, thiazole-based compounds, thiuram-based compounds, thiourea-based compounds, dithiocarbamic acid-based compounds, aldehyde-amine-based compounds, aldehyde-ammonia-based compounds, imidazoline-based compounds, and xanthate-based compounds. These vulcanization accelerators may be used alone or in combination of two or more. The vulcanization accelerator is usually contained in an amount of 0.1 to 15 parts by mass, preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the rubber component.

[0088] When the rubber composition contains sulfur or a sulfur compound as a crosslinking agent for crosslinking (vulcanizing) the rubber component, the rubber composition may further contain a vulcanization aid. Examples of the vulcanization aid include fatty acids such as stearic acid, metal oxides such as zinc oxide, and fatty acid metal salts such as zinc stearate. These vulcanization aids may be used alone or in combination of two or more. The vulcanization aid is usually contained in an amount of 0.1 to 15 parts by mass, preferably 1 to 10 parts by mass, based on 100 parts by mass of the rubber component.

[0089] When the rubber composition contains silica as a filler, it is preferable that the rubber composition further contains a silane coupling agent, such as a sulfide compound, a mercapto compound, a vinyl compound, an amino compound, a glycidoxy compound, a nitro compound, or a chloro compound. These silane coupling agents may be used alone or in combination of two or more. The silane coupling agent is preferably contained in an amount of 0.1 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, and even more preferably 1 to 15 parts by mass, based on 100 parts by mass of silica. When the content of the silane coupling agent is within the above range, dispersibility, coupling effect, and reinforcing property are improved.

[0090] The rubber composition may contain, as needed, a softener such as silicone oil, aromatic oil, TDAE (Treated Distilled Aromatic Extracts), MES (Mild Extracted Solvates), RAE (Residual Aromatic Extracts), process oil such as paraffin oil or naphthene oil, aliphatic hydrocarbon resin, alicyclic hydrocarbon resin, C9 resin, rosin resin, coumarone-indene resin, or phenol resin, for the purpose of improving processability, flowability, etc., within a range that does not impair the effects of the present invention. When the rubber composition contains the process oil as a softener, the content thereof is preferably less than 50 parts by mass per 100 parts by mass of the rubber component.

[0091] The rubber composition may contain additives such as antiaging agents, waxes, antioxidants, lubricants, light stabilizers, scorch inhibitors, processing aids, colorants such as pigments and dyes, flame retardants, antistatic agents, matting agents, antiblocking agents, UV absorbers, release agents, foaming agents, antibacterial agents, antifungal agents, and fragrances, as necessary, for the purpose of improving weather resistance, heat resistance, oxidation resistance, and the like, within a range that does not impair the effects of the present invention. Examples of the antioxidant include hindered phenol compounds, phosphorus compounds, lactone compounds, and hydroxyl compounds. Examples of the antiaging agents include amine-ketone compounds, imidazole compounds, amine compounds, phenol compounds, sulfur compounds, and phosphorus compounds. These additives may be used alone or in combination of two or more.

[0092] As a method for producing the rubber molded body, for example, the reinforcing fiber is embedded in the unvulcanized rubber composition, and the rubber composition is vulcanized to obtain a molded body in which the surface-modified fiber and the rubber component are bonded via the adhesive component.

[0093] The brake oil hose for automobiles may, for example, have an inner rubber layer and an outer rubber layer, with one or two reinforcing layers made of the reinforcing fibers between the inner rubber layer and the outer rubber layer. Examples of the rubber components constituting the inner rubber layer and the outer rubber layer include those mentioned above. Among them, examples of the rubber components constituting the inner rubber layer include EPDM, SBR, etc., and examples of the rubber components constituting the outer rubber layer include EPDM, CR, etc. The reinforcing layer can be formed by braiding reinforcing fibers. In the method for producing the brake oil hose, a reinforcing layer (first reinforcing layer) made by braiding the reinforcing fibers is formed on the outer surface of the inner rubber layer. When forming two reinforcing layers, an intermediate rubber layer may be further formed on the outer surface of the first reinforcing layer, and a reinforcing layer (second reinforcing layer) made by braiding the reinforcing fibers may be formed on the outer surface of the intermediate rubber layer. Then, the outer rubber layer is formed on the outer surface of the reinforcing layer (first reinforcing layer or second reinforcing layer), and the hose can be produced by vulcanizing the outer rubber layer. The vulcanization temperature can be appropriately selected depending on the type of constituent materials of each layer of the brake oil hose, but it is preferable that the vulcanization temperature be 200°C or lower from the viewpoint of suppressing deterioration of the rubber and reinforcing fibers and improving the adhesive strength between the rubber and the reinforcing fibers. EXAMPLES

[0094] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0095] <Production of modified conjugated diene rubber> Production of modified conjugated diene rubber having a monomer unit represented by the following formula (1a): [ka]

[0096] Production Example 1: Production of modified conjugated diene rubber (A-1) A 5L autoclave that was thoroughly dried was replaced with nitrogen, and 756g of hexane and 122.3g of n-butyllithium (17% by mass hexane solution) were charged. The temperature was raised to 50°C, and then 1344g of butadiene was successively added while controlling the polymerization temperature to 50°C under stirring conditions, and polymerization was carried out for 1 hour. Methanol was then added to terminate the polymerization reaction, and a polymer solution was obtained. Water was added to the obtained polymer solution, and the mixture was stirred, and the polymer solution was washed with water. After stopping the stirring, it was confirmed that the polymer solution phase and the water phase were separated, and then the water was separated. The polymer solution after washing was vacuum dried at 70°C for 24 hours to obtain an unmodified liquid polybutadiene (A'-1). Next, 600 g of the obtained unmodified liquid polybutadiene (A'-1) was charged into a 1 L autoclave that had been purged with nitrogen, and 30 g of maleic anhydride and 0.6 g of N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (product name "Nocrac 6C", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) were added, and the mixture was reacted at 170°C for 24 hours to obtain maleic anhydride-modified liquid polybutadiene (A-1).

[0097] Production Example 2: Production of modified conjugated diene rubber (A-2) A 5L autoclave that was thoroughly dried was purged with nitrogen, and 1260g of hexane and 36.3g of n-butyllithium (17% by mass hexane solution) were charged. The temperature was raised to 50°C, and then 1260g of butadiene was added successively under stirring conditions while controlling the polymerization temperature to 50°C, and polymerization was carried out for 1 hour. Methanol was then added to terminate the polymerization reaction, and a polymer solution was obtained. Water was added to the obtained polymer solution, and the mixture was stirred, and the polymer solution was washed with water. After stopping the stirring, it was confirmed that the polymer solution phase and the water phase were separated, and then the water was separated. The polymer solution after washing was vacuum dried at 70°C for 24 hours to obtain an unmodified liquid polybutadiene (A'-2). Next, 500 g of the obtained unmodified liquid polybutadiene (A'-2) was charged into a 1 L autoclave that had been purged with nitrogen, and 25 g of maleic anhydride and 0.5 g of N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (product name "Nocrac 6C", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) were added, and the mixture was reacted at 170°C for 24 hours to obtain maleic anhydride-modified liquid polybutadiene (A-2).

[0098] Production Example 3: Production of modified conjugated diene rubber (A-3) A 5L autoclave that was thoroughly dried was purged with nitrogen, and 1140g of hexane and 20.9g of n-butyllithium (17% by mass hexane solution) were charged. The temperature was raised to 50°C, and then 1390g of butadiene was successively added while controlling the polymerization temperature to 50°C under stirring conditions, and polymerization was carried out for 1 hour. Methanol was then added to terminate the polymerization reaction, and a polymer solution was obtained. Water was added to the obtained polymer solution, and the mixture was stirred, and the polymer solution was washed with water. After stopping the stirring, it was confirmed that the polymer solution phase and the water phase were separated, and then the water was separated. The polymer solution after washing was vacuum dried at 70°C for 24 hours to obtain an unmodified liquid polybutadiene (A'-3). Next, 500 g of the obtained unmodified liquid polybutadiene (A'-3) was charged into a 1 L autoclave that had been purged with nitrogen, and 25 g of maleic anhydride and 0.5 g of N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (product name "Nocrac 6C", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) were added, and the mixture was reacted at 170°C for 24 hours to obtain maleic anhydride-modified liquid polybutadiene (A-3).

[0099] Production Example 4: Production of modified conjugated diene rubber (A-4) To 525 g of the obtained maleic anhydride modified liquid polybutadiene (A-3), 9.0 g of methanol was added and reacted at 80° C. for 6 hours to obtain a monomethyl maleate modified liquid polybutadiene (A-4).

[0100] Production Example 5: Production of modified conjugated diene rubber (A-5) To 525 g of the obtained maleic anhydride modified liquid polybutadiene (A-2), 8.5 g of methanol was added, and the mixture was reacted at 80° C. for 6 hours to obtain a monomethyl maleate modified liquid polybutadiene (A-5).

[0101] The methods for measuring and calculating the properties of the modified conjugated diene rubber are as follows. The results are shown in Table 1. <Methods for measuring weight average molecular weight, number average molecular weight and molecular weight distribution> The weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the modified conjugated diene rubber were determined as standard polystyrene equivalent values ​​by GPC (gel permeation chromatography) using the following measuring device and conditions: · Apparatus: Tosoh Corporation GPC device "GPC8020" Separation column: Tosoh Corporation's "TSKgelG4000HXL" Detector: Tosoh Corporation "RI-8020" Eluent: Tetrahydrofuran ·Eluent flow rate: 1.0ml / min Sample concentration: 5mg / 10ml Column temperature: 40℃

[0102] <Melt viscosity measurement method> The melt viscosity of the modified conjugated diene rubber at 38° C. was measured using a Brookfield viscometer (manufactured by BROOKFIELD ENGINEERING LABS. INC.).

[0103] <Method of measuring glass transition temperature> 10 mg of the modified conjugated diene rubber was placed in an aluminum pan, and a thermogram was measured by differential scanning calorimetry (DSC) at a heating rate of 10° C. / min. The DDSC peak top value was taken as the glass transition temperature.

[0104] <Method of measuring vinyl content> The vinyl content of the modified conjugated diene rubber was determined by the 1 Measurements were performed using H-NMR (500 MHz) at a sample / d2Cl concentration of 50 mg / 1 mL and an accumulation count of 1024. The vinyl content was calculated from the area ratio of the peak of the double bond derived from the vinylated diene compound to the peak of the double bond derived from the non-vinylated diene compound in the obtained spectrum.

[0105] <Average number of hydrogen-bonding functional groups per molecule> The average number of hydrogen-bonding functional groups per molecule of the modified conjugated diene rubber was calculated from the equivalent weight (g / eq) of the hydrogen-bonding functional groups of the modified conjugated diene rubber and the number average molecular weight Mn in terms of styrene by the following formula. Average number of hydrogen-bonding functional groups per molecule = [(number average molecular weight (Mn)) / (molecular weight of styrene unit) x (average molecular weight of conjugated diene and other monomer units other than conjugated diene contained as necessary)] / (equivalent weight of hydrogen-bonding functional group) The method for calculating the equivalent weight of the hydrogen-bonding functional group can be appropriately selected depending on the type of the hydrogen-bonding functional group.

[0106] The average number of hydrogen-bonding functional groups per molecule of the maleic anhydride-modified conjugated diene rubber and the monomethyl maleate-modified conjugated diene rubber was calculated by determining the acid value of the maleic anhydride-modified conjugated diene rubber and the monomethyl maleate-modified conjugated diene rubber and calculating the equivalent weight (g / eq) of the hydrogen-bonding functional group from the acid value. After the modification reaction, the sample was washed four times with methanol (5 mL per 1 g of sample) to remove impurities such as antioxidants, and then dried under reduced pressure at 80° C. for 12 hours. 180 mL of toluene and 20 mL of ethanol were added to 3 g of the sample after the modification reaction to dissolve it, and then neutralized with a 0.1 N ethanol solution of potassium hydroxide, and the acid value was calculated using the following formula. Acid value (mgKOH / g)=(AB)×F×5.611 / S A: Amount of 0.1N potassium hydroxide ethanol solution added for neutralization (mL) B: Amount of 0.1N potassium hydroxide ethanol solution dropped into a blank containing no sample (mL) F: Potency of 0.1N potassium hydroxide in ethanol S: mass of weighed sample (g)

[0107] From the acid value, the mass of the hydrogen-bonding functional group contained per gram of the maleic anhydride-modified conjugated diene rubber and the monomethyl maleate-modified conjugated diene rubber was calculated using the following formula, and the mass of the non-functional group (polymer main chain mass) contained per gram of the maleic anhydride-modified conjugated diene rubber and the monomethyl maleate-modified conjugated diene rubber was calculated. Then, the equivalent weight (g / eq) of the hydrogen-bonding functional group was calculated using the following formula. [Hydrogen-bonding functional group mass per 1 g] = [acid value] / [56.11] x [hydrogen-bonding functional group molecular weight] / 1000 [Mass of polymer main chain per 1g] = 1 - [Mass of hydrogen-bonding functional group per 1g] [Equivalent weight of hydrogen-bonding functional group] = [mass of polymer main chain per 1 g] / ([mass of hydrogen-bonding functional group per 1 g] / [molecular weight of hydrogen-bonding functional group])

[0108] [Table 1]

[0109] <Constituent materials of the surface modification layer (surface modification agent)> By mixing the components according to the formulations in Table 2, the constituent materials of the surface modification layer (surface modification agents B-1 to B-9) were prepared. [Table 2]

[0110] Details of the compounds listed in Table 2 are as follows. ·Blocked isocyanate compounds Meikanate DM-3031 CONC (Meisei Chemical Industry Co., Ltd., pure content 54% by mass) Epoxy compounds Denacol EX-614B (manufactured by Nagase Chemtec Corporation, pure content 100% by mass) Oxazoline-containing compounds Epocross WS-700 (manufactured by Nippon Shokubai Co., Ltd., purity 25% by mass) Carbodiimide group-containing compounds Carbodilite Prototype (Nisshinbo Chemical Co., Ltd., pure content 40% by mass) Sodium acrylate compounds AQUALIC DL-453 (manufactured by Nippon Shokubai Co., Ltd., purity 35% by mass) Ethyleneimine compounds Epomin SP-200 (manufactured by Nippon Shokubai Co., Ltd., pure content 100% by mass) Diamide-type cationic compounds Adekamin SF-201 (manufactured by ADEKA Corporation, purity 80% by mass)

[0111] <Dilute solution of conjugated diene rubber> Each of the modified conjugated diene rubbers shown in Table 1 was diluted with a fatty acid ester or mineral oil to prepare a 25% by mass solution. The fatty acid ester is a polyol fatty acid ester (trimethylolpropane tricaprylate) with a vapor pressure of 1.7×10 at 20°C. -7The mineral oil used had a vapor pressure of 7.0×10 at 20°C, a flash point of 258°C, and was non-volatile. -3 The solvent used had a viscosity of 1.0 Pa, a flash point of 158°C, and was non-volatile.

[0112] <Example 1> PET fibers (total fineness: 1100 dtex, single filament fineness: 6.10 dtex), which are polyester-based fibers, were immersed in the surface modifier (B-1), and then the liquid was squeezed out with a roller. The resulting fiber was then dried at 140°C for 60 seconds and further heat-treated at 240°C for 60 seconds to produce a surface-modified fiber. Next, a diluted solution of the modified conjugated diene rubber was prepared so as to have the composition and amount of adhesion shown in Table 3, and then the diluted solution was applied to the surface-modified fiber using an oiling guide and wound up. After that, the fiber was allowed to settle at room temperature (20°C) for 3 days, and then twisted at a twist rate of 80 T / m to produce a reinforcing fiber.

[0113] <Examples 2 to 7 and Comparative Examples 1 to 4> A reinforcing fiber was prepared in the same manner as in Example 1, except that the surface modification layer, adhesive layer, and their adhesion amounts were changed as shown in Table 3.

[0114] <Reference example 1> PET fibers (total fineness 1100 dtex, single filament fineness 6.10 dtex), which are polyester-based fibers, were immersed in the pretreatment liquid described below, and the liquid was squeezed out with a roller, applied, dried at 140°C for 60 seconds, and further heat-treated at 240°C for 60 seconds. After applying RFL, the yarn was dried at 140°C for 60 seconds and then heat-treated at 240°C for 60 seconds to obtain a treated yarn. The treated yarn was twisted at a twist rate of 80 T / m to produce a reinforcing fiber. The pretreatment liquid and RFL liquid used were prepared by the following methods.

[0115] [Preparation of RFL pretreatment solution] Water: 96.96 parts by mass Blocked isocyanate: 2.29 parts by mass Epoxy compound: 0.75 parts by mass The pretreatment liquid was prepared using a blocked isocyanate and an epoxy resin. Note that the blocked isocyanate used was "Meikanote DM-3031 CONC" manufactured by Meisei Chemical Industry Co., Ltd., and the epoxy resin used was "Denacol EX-614B" manufactured by Nagase ChemteX Corporation.

[0116] [Adjustment of RFL liquid] A liquid Water: 524 parts by mass Resorcinol: 15 parts by weight Formaldehyde (effective content 37% by mass): 16 parts by mass Sodium hydroxide solution (effective content 10% by mass): 4 parts by mass The above solution A was aged at 25° C. for 6 hours.

[0117] B liquid SBR latex (effective content 40% by mass): 207 parts by mass Vinylpyridine modified SBR latex (effective content 40% by mass): 233 parts by mass The above-mentioned solution B and the aged solution A were mixed, and then aged at a temperature of 25° C. for 16 hours to produce an RFL solution.

[0118] <Zeta potential measurement> The zeta potential of the fiber surface of the surface-modified fibers obtained in Examples 1 to 7 and Comparative Examples 1 to 4 was measured using a flat cell at pH = 7 and a temperature of 25°C with a zeta potential / particle size measurement system ELSZ-1000 (manufactured by Otsuka Electronics Co., Ltd.). Specifically, the fibers were arranged closely together in a flat cell, and a dispersion of monitor particles (polystyrene particles coated with hydroxypropyl cellulose [manufactured by Otsuka Electronics Co., Ltd.]) dispersed in a 10 mM sodium chloride (NaCl) solution was poured into the flat cell. Electrophoresis was performed under the condition of an applied voltage of 80 V.

[0119] <Measurement of adhesive strength between reinforcing fiber and EPDM rubber> For the reinforcing fibers obtained in Examples 1 to 7, Comparative Examples 1 to 4, and Reference Example 1, evaluation sheets were prepared by the following method, and the force (N / 25.4 mm) required to T-separate the reinforcing fibers from the rubber was measured and evaluated as rubber adhesion. The results are shown in Table 3. In the evaluation results of the rubber adhesive strength, a larger value indicates a stronger adhesive strength between the reinforcing fiber and the rubber. The adhesive sheet was prepared as follows.

[0120] [Preparation of evaluation sheet] The reinforcing fibers prepared in the Examples, Comparative Examples, and Reference Examples were arranged and fixed on a masking tape in a curtain-like manner so that the reinforcing fibers did not overlap each other, and then this was layered on an unvulcanized rubber composition prepared separately using EPDM rubber according to the following compounding composition. Then, the rubber composition was heated at 150°C under a pressure of 20 kg / cm. 2 The mixture was press-vulcanized for 30 minutes under the above conditions to prepare a sheet for evaluation.

[0121] [EPDM unvulcanized rubber compound composition] EPDM rubber: 100 parts by weight Filler (carbon black): 60 parts by weight Softener (paraffin-based process oil): 20 parts by weight Crosslinking agent (sulfur powder): 1.5 parts by weight Vulcanization aid (zinc oxide type 2, stearic acid): 6 parts by mass Vulcanization accelerator (thiazole type, thiuram type): 1.5 parts by mass

[0122] [Table 3]

[0123] <Examples 8 to 16 and Comparative Examples 5 to 9> Reinforcing fibers were produced in the same manner as in Example 1, except that the fibers, surface modification layer, adhesive layer, and their attachment amounts were changed as shown in Table 4. In addition to the polyester-based fibers, nylon fibers (total fineness 1100 dtex, single yarn fineness 6.10 dtex), which are polyamide-based fibers, and vinylon fibers (total fineness 1330 dtex, single yarn fineness 6.65 dtex, "Kuralon 1239" manufactured by Kuraray Co., Ltd.) were used as fiber types.

[0124] <Reference example 2> A reinforcing fiber was produced in the same manner as in Reference Example 1, except that no final twist was applied.

[0125] <Measurement of adhesion between reinforcing fiber and NR / SBR rubber> For the reinforcing fibers obtained in Examples 8 to 16, Comparative Examples 5 to 9, and Reference Example 2, evaluation sheets were prepared by the following method, and the force (N / 25.4 mm) required to perform T-type peeling of the reinforcing fibers from the rubber was measured and evaluated as rubber adhesion. The results are shown in Table 4. In the evaluation results of rubber adhesion, a larger numerical value indicates a stronger adhesive strength between the reinforcing fibers and rubber. The adhesive sheets were prepared as follows.

[0126] [Preparation of evaluation sheet] The reinforcing fibers prepared in the above-mentioned Examples, Comparative Examples, and Reference Examples were arranged and fixed on a masking tape in a curtain-like manner so that the reinforcing fibers did not overlap each other, and then this was layered on an unvulcanized rubber composition prepared separately using NR / SBR rubber according to the following blending composition. Then, the rubber composition was laminated at 150°C under a pressure of 20 kg / cm. 2 The mixture was press-vulcanized for 30 minutes under the above conditions to prepare a sheet for evaluation.

[0127] [NR / SBR unvulcanized rubber compound composition] NR rubber: 70 parts by weight SBR rubber: 41.25 parts by weight Filler (carbon black): 45 parts by weight Vulcanizing agent (sulfur powder): 3.5 parts by weight Vulcanization aid (zinc oxide, stearic acid): 6 parts by mass Vulcanization accelerator (thiazole type): 1 part by mass

[0128] [Table 4]

[0129] Example 17: Method for Treating Twisted Cords Two PET fibers (total fineness 1100 dtex, single yarn fineness 6.10 dtex), a polyester fiber, were twisted 470 times / m and twisted 470 times / m to produce a fiber cord. The twisted cord was immersed in the surface modifier (B-1), and then squeezed with a roller. The obtained fiber cord was dried at 140°C for 60 seconds, and further heat-treated at 240°C for 60 seconds to produce a fiber cord. Next, the cord was immersed in an emulsion composition mainly composed of a modified conjugated diene rubber shown in Table 5, and then squeezed with a roller, dried at 140°C for 60 seconds, and then wound up. The content of the modified conjugated diene rubber in the emulsion composition was 10% by mass.

[0130] <Examples 18 and 19 and Comparative Example 10> A reinforcing fiber was prepared in the same manner as in Example 17, except that the surface modification layer, adhesive layer, and their adhesion amounts were changed as shown in Table 5.

[0131] <Reference example 3> A reinforcing fiber was prepared in the same manner as in Reference Example 1, except that twisted PET fiber cords were used.

[0132] <Rubber adhesive strength measurement> For the reinforcing fibers obtained in Examples 17 to 19, Comparative Example 10, and Reference Example 3, evaluation specimens were prepared by the following method, and the force (N / 3 fibers) required to perform T-type peeling of the reinforcing fibers from the rubber was measured and evaluated as rubber adhesion. The results are shown in Table 5. In the evaluation results of rubber adhesion, a larger numerical value indicates a stronger adhesive strength between the reinforcing fibers and rubber. The adhesion specimens were prepared as follows.

[0133] <Preparation of evaluation specimen> The reinforcing fibers prepared in the above-mentioned Examples, Comparative Examples, and Reference Examples were arranged in a line with a certain interval in the unvulcanized NR / SBR rubber composition prepared by the above-mentioned blending. Then, the fibers were subjected to a test at 150°C under a pressure of 20 kg / cm. 2 Adhesion specimens were prepared by press-vulcanizing the mixture for 30 minutes under the above conditions.

[0134] [Table 5]

[0135] As is clear from the results of the Examples and Comparative Examples, the present invention makes it possible to obtain surface-modified fibers and reinforcing fibers that have excellent adhesion to rubber. In particular, the present invention makes it possible to firmly bond fibers and rubber without using an adhesive whose main components are resorcinol-formaldehyde resin and rubber latex.

Claims

1. A surface-modified fiber comprising a fiber and a surface-modified layer covering at least a portion of the surface of the fiber, the surface of the surface-modified layer having a solid surface zeta potential of -20.0 to 30.0 mV, and the fiber being a polyvinyl alcohol-based fiber.

2. The surface-modified fiber of claim 1 , wherein the surface-modified layer comprises a compound having a nitrogen-containing functional group.

3. The surface-modified fiber according to claim 1 or 2, wherein the surface-modified layer contains a compound having a functional group derived from one or more selected from an oxazoline group, an oxazolidinone group, a carbodiimide group, a carbamide group, an amino group, and an aziridine group.

4. The surface-modified fiber according to any one of claims 1 to 3, wherein the amount of the surface-modified layer is 0.01 to 5.0 parts by mass per 100 parts by mass of the fiber used as the raw material.

5. A reinforcing fiber having a surface-modified fiber according to any one of claims 1 to 4 and an adhesive layer containing a conjugated diene rubber covering at least a portion of the surface of the surface-modified fiber.

6. The reinforcing fiber according to claim 5 , wherein the conjugated diene rubber has a number average molecular weight (Mn) of more than 2,000 and not more than 120,000.

7. 7. The reinforcing fiber according to claim 5, wherein the conjugated diene rubber has, in its molecule, a monomer unit derived from at least one selected from butadiene, isoprene, and farnesene.

8. The reinforcing fiber according to any one of claims 5 to 7, wherein the conjugated diene rubber is a modified conjugated diene rubber having a hydrogen-bonding functional group in a part of the conjugated diene rubber, and the hydrogen-bonding functional group is at least one selected from a hydroxy group, an epoxy group, an aldehyde group, an acetalized product of an aldehyde group, a carboxy group, a salt of a carboxy group, an esterified product of a carboxy group, an acid anhydride of a carboxy group, a silanol group, an esterified product of a silanol group, an amino group, an imidazole group, and a mercapto group.

9. The reinforcing fiber according to any one of claims 5 to 8, wherein the adhesive layer further contains oil, and the oil has a vapor pressure of 10 Pa or less at 20°C.

10. A molded body using the reinforcing fiber according to any one of claims 5 to 9.

11. The molded article according to claim 10, further comprising a rubber layer.

12. The molded article according to claim 10 or 11, which is a tire, a belt or a hose.

13. A molded body having the polyvinyl alcohol-based fiber, the surface modification layer having a solid surface zeta potential of -20.0 to 30.0 mV on the surface, the adhesive layer, and the rubber layer in this order, wherein the adhesive strength between the adhesive layer and the rubber layer is 70 N or more per 25.4 mm width.

Citation Information

Patent Citations

  • Japanese graphic character study apparatus

    JP1983005777A

  • Fiber cord for reinforcement and rubber-cord composite using the same and cord treating agent

    JP1999081075A

  • Method for producing water-repellent fiber product

    JP2017210704A

  • Surface-modified fiber, reinforcing fiber, and molded body using same

    JP7604393B2

  • Method For Producing A Masterbatch Of Synthetic Diene Elastomer And Carbonated Filler

    US20180079874A1

Cited By

  • Adhesive composition

    JP7835340B1